Risk of Acute Myocardial Infarction in Patients with Systemic Lupus Erythematosus Compared with the General Population: A Systematic Review and Meta-Analysis - Eli Novi; Wahyudi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Patients with systemic lupus erythematosus (SLE) are at substantially elevated risk of acute myocardial infarction (AMI) compared with the general population, attributable to a complex interplay of accelerated atherosclerosis, coronary microvascular dysfunction, antiphospholipid antibody-mediated thrombosis, and dysregulated innate immunity. Pooled estimates across published meta-analyses have not been formally synthesised. Methods: A systematic review and meta-analysis were conducted in accordance with PRISMA 2020 guidelines. PubMed, MEDLINE, and EMBASE were searched through 2 April 2026 for studies reporting the relative risk (RR) of AMI in SLE patients versus the general population. Three eligible meta-analyses providing RR estimates were identified. Data were pooled using the DerSimonian-Laird random-effects model with Hartung-Knapp-Sidik-Jonkman (HKSJ) adjustment, implemented in R 4.5.3 (packages meta v8.2-1 and metafor v4.8-0). Heterogeneity was assessed using Cochran’s Q and I². Publication bias was evaluated using Egger’s precision-effect test. A sensitivity analysis incorporating all five eligible comparative studies with mixed effect measures (RR, rate ratio, OR) was performed, alongside subgroup analysis by study design. Results: Three meta-analyses incorporating 24 to 46 primary studies and representing data from approximately 168,000 SLE patients were eligible for the primary pool. The pooled RR of AMI in SLE patients was 2.95 (95% CI 2.57–3.39; p < 0.001). Heterogeneity was negligible (I² = 0.0%; Q = 0.04, p = 0.98; τ² = 0.000). Weights were: Bello et al. 2023 (61.5%), Yazdany et al. 2020 (31.5%), Gu et al. 2019 (7.0%). Sensitivity analysis, including all five comparative studies (mixed measures), yielded a pooled effect of 5.27 (95% CI 2.91–9.53) with substantial heterogeneity (I² = 92.7%, Q = 55.11, p < 0.001), consistent with expected heterogeneity from mixing incompatible effect measures. Subgroup analysis by design showed Q-difference = 55.07 (df = 2, p < 0.001). Egger’s test was non-significant (t = 1.63, p = 0.35). Conclusion: SLE patients face approximately a three-fold elevated risk of AMI compared with the general population, a finding derived from homogeneous, high-quality evidence and confirmed by sensitivity analyses. These findings underscore the need for systematic, SLE-specific cardiovascular risk management, including judicious use of hydroxychloroquine, lipid-lowering therapy, and multidisciplinary cardiorheumatology follow-up.